Response of Women Activists To the Implementation of the Mayor of Banda Aceh's Instructions NO. 2 of 2015 - Manswab Mahsen Abdulrahman; Rafiqa Rafiqa (Program Pascasarjana UIN Sumatera Utara Medan, 2017)
Based on the theory of social construction, justice, Women in Development (WID) and Women and Development (WID). This paper tends to responses of women activists againts the mayor of Banda Aceh Instructions no 2 yers 2015. sources of data obtained through legal research are empirical. Through data analysis and discussion, research shows that (1) The results of responses of women activists in Banda Aceh contributed to broaden understanding of the gender perspective of Islamic sharia in Aceh is KKTGA organization, disagree with the imposition of hours of night work for women, because it obstructs women's profession, and the violence is not outside but at home. Aceh GeRAK organization disagrees with the reasons enough that rule does not need to be applied because of existing tradition. Different from the organization LKBHuWK even agrees with the premise of maintaining the dignity of women. According to KKTGA that Islamic syari'at is a gender perspective rather difficult to implement in Aceh for Acehnese understand the law only written in the Qanun. (2) This case, these three organizations to criticize the wisdom do not need to be restricted, the law sharply upwards and downwards blunt need evaluation, and must have their own consciousness. (3) Three of these organizations provide solutions including Islamic law should be firm, more attention to small communities and active in socializing any regulations made.